PENERAPAN INTERNAL AUDITOR UNTUK MENCAPAI KINERJA MANAJEMEN PADA HOTEL GRAND ANTARES MEDAN - MARKUS DODDY SIMANJUNTAK (JURNAL ILMIAH KOHESI, 2021)
The purpose of this research is to implement the internal auditor function in achieving management performance at GrandAntares Hotel Medan. From the results of the research showed the internal auditor at Grand Antares Hotel Medan has aposition that is aligned with the organizational unit that became the object of the audit, namely the operational part of guestservices. The assignment of internal auditors must be based on the permission of the internal control manager and also thedirector / managing director of the company. Internal control management is the direct supervisor of the internal auditor. Theinternal function of auditors in the company is able to find weaknesses and frauds that occur in the policies set by thecompany's management. Guest service at Grand Antares Hotel Medan is less effective because of the weakness in thesystem. Internal auditors can find weaknesses or fraud in the operational activities of Grand Antares Hotel Medan, so byconducting such audits can improve the efficiency of management performance.